Welfare and stress in salmonids: blood based diagnostics in terms of feeding stress - Seibel, Henrike (Christian-Albrechts-Universität zu Kiel, 2024)
Animal welfare aspects in aquaculture concern the well-being of aquatic animals in a controlled environment. Good practices are important to assess the responses of fish to environmental and handling conditions and to improve stress management. Soybean meal-induced enteritis (SBMIE) is used here to investigate feeding stress. This study investigates whether blood is suitable for detecting stress and well-being in fish. Rainbow trout and Atlantic salmon were used as research species. The introduction to blood diagnostics summarises the current state of research and describes plasma tests and multiparametric analyses for the assessment of well-being and disease in fish. The comparison of molecular stress markers with classical methods such as cortisol determination shows which markers indicate feeding stress. In a 56-day feeding trial, the influence of soybean meal on rainbow trout was investigated and compared with haematocrit, plasma cortisol and molecular stress markers being analysed. Another study investigated the effect of a plant-based diet on the immune response of trout. Simulated handling stress showed that blood tests provide early information about feeding stress before performance parameters change. However, a control group is essential for a realistic interpretation of the results. In the final study, the initially established molecular markers were used to test the potential of a feed additive for stress reduction and immune stimulation. The results were successfully transferred to Atlantic salmon, demonstrating the applicability of blood diagnostics in feeding stress. The work shows that blood tests provide valuable information even before other changes in performance or behaviour become apparent. Tierschutzaspekte in der Aquakultur betreffen das Wohlbefinden von Wassertieren in kontrollierter Umgebung. Gute Praktiken sind wichtig, um die Reaktionen von Fischen auf Umwelt- und Handhabungsbedingungen zu bewerten und das Stressmanagement zu verbessern. Die Sojabohnenmehl-induzierte Enteritis ...